Association of an HLA‐G 14‐bp Insertion/Deletion polymorphism with high HBV replication in chronic hepatitis. Issue 10 (26th January 2015) - Laaribi, A. B.; Zidi, I.; Hannachi, N.; Ben Yahia, H.; Chaouch, H.; Bortolotti, D.; Zidi, N.; Letaief, A.; Yacoub, S.; Boudabous, A.; Rizzo, R.; Boukadida, J.
Summary Identification of an HLA‐G 14‐bp Insertion/Deletion (Ins/Del) polymorphism at the 3′ untranslated region of HLA‐G revealed its importance in HLA‐G mRNA stability and HLA‐G protein level variation. We evaluated the association between the HLA‐G 14‐bp Ins/Del polymorphism in patients with chronic Hepatitis B virus (HBV) infection in a case–control study. Genomic DNA was extracted from 263 patients with chronic HBV hepatitis and 246 control subjects and was examined for the HLA‐G 14‐bp Ins/Del polymorphism by PCR. The polymorphic variants were genotyped in chronic HBV seropositive cases stratified according to HBV DNA levels, fibrosis stages and in a control population. There was no statistical significant association between the 14‐bp Ins/Del polymorphism and increased susceptibility to HBV infection neither for alleles (P = 0.09) nor for genotypes (P = 0.18). The stratification of HBV patients based on HBV DNA levels revealed an association between the 14‐bp Ins/Del polymorphism and an enhanced HBV activity with high HBV DNA levels. In particular, the Ins allele was significantly associated with high HBV DNA levels (P = 0.0024, OR = 1.71, 95% CI 1.2–2.4). The genotype Ins/Ins was associated with a 2.5‐fold (95% CI, 1.29–4.88) increased risk of susceptibility to high HBV replication compared with the Del/Del and Ins/Del genotypes. This susceptibility is linked to the presence of two Ins alleles. No association was observed between the 14‐bp Ins/Del polymorphism and fibrosis stage of HBV infection. We observed an association between the 14‐bp Ins/Del polymorphism and high HBV replication characterized by high HBV DNA levels in chronic HBV patients. These results suggest a potential prognostic value for disease outcome evaluation.